Constructing femininity in the book of Jubilees - Syfox, Chontel (Biblical interpretation series, 2025)
"A striking feature of the book of Jubilees is the visibility it gives to women in comparison to Genesis, with the matriarchs especially seeming to play an outsized role in the rewriting. Utilising approaches drawn from the fields of gender and feminist studies, Constructing Femininity in the Book of Jubilees interrogates the motives and priorities that guided the rewriter in his re-presentation of the matriarchs, asking to what extent the treatment of these characters was unique to this text and its author's attitude towards women or typical of the then literary Zeitgeist"-- Provided by publisher